2020
DOI: 10.1002/ehf2.12650
|View full text |Cite
|
Sign up to set email alerts
|

Double‐chambered right ventricle complicated by hypertrophic obstructive cardiomyopathy diagnosed as Noonan syndrome

Abstract: We present a case of double-chambered right ventricle (DCRV) complicated by hypertrophic obstructive cardiomyopathy (HOCM) in KRAS mutation-associated Noonan syndrome. The diagnosis was incidental and made during diagnostic testing for an intradural extramedullary tumour. Spinal compression, if not surgically treated, may cause paralysis of the extremities. We decided to pursue pharmacological therapy to control biventricular obstructions and reduce the perioperative complication rate. We initiated treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, DCRV complicated by HCM is an extremely rare coexistence. Several cases reported this unique condition complicated with HCM (2,5,6). With respect to the combination of arrhythmias, Alvarez et al reported that, in two adult patients diagnosed with DCRV, complicated by sustained monomorphic ventricular tachycardia, tachycardia did not reoccur after surgical excision of the abnormal muscle bundles (7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, DCRV complicated by HCM is an extremely rare coexistence. Several cases reported this unique condition complicated with HCM (2,5,6). With respect to the combination of arrhythmias, Alvarez et al reported that, in two adult patients diagnosed with DCRV, complicated by sustained monomorphic ventricular tachycardia, tachycardia did not reoccur after surgical excision of the abnormal muscle bundles (7).…”
Section: Discussionmentioning
confidence: 99%
“…Since some patients with DCRV do not experience progressive RVOT blockage during the normal course of the disease, basic follow-up is sufficient for patients with no significant lesions and little or no pressure gradient in the RV (4,16,17). Negative inotropic drugs, such as beta-blockers and calcium channel antagonists, may be effective in improving symptoms (2,12). If the obstruction worsens during follow-up, surgical repair may be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al described an 80-year-old HCM-patient with DCRV who experienced recurrent hypotension and chest discomfort during hemodialysis [3]. Yamamoto reported most probably the first case of a 47-years-old DCRV-patient coexisting with severe left ventricle outflow tract obstruction (LVOTO) [4]. We describe a HCM-patient in whom DCRV was diagnosed in adulthood.…”
mentioning
confidence: 88%